The means of expression and semantics of emotive words in Turkic languages - Nurila G. Shaymerdinova, Nazgul R. Balabekova,; Adambayeva, Gulbarshyn M.; Begimova, Gulzhanat A. (Opción, 2019)
The study aims to investigate the means of expression and semantics of emotive words in Turkic languages via onomasiological and semasiological approaches. As a result, this paper deals with the analysis emotive words as units of language expressing the emotional-mental state of a person, based on the materials of the Kazakh and Turkish languages. In conclusion, emotivity is a mental state, which appears in accordance with the satisfaction degree of a person in different life situations.